Synthesis and characterization of value added catalysts zeolite beta using environmentally detrimental flyash - Kasture, M. W.; Bokade, Vijay V.; Joshi, P. N.; Kumar, R. (From Zeolites to Porous Mof Materials: the 40th Anniversary of International Zeolite Conference, Proceedings of the 15th International Zeolite Conference, 2007)
Fly ash is a major byproduct of Thermal power plant, which makes a lot of pollution to the environment due to its fineness. When a large amount of fly ash is dumped in the places near to power plants, it mixes in all segment of environment like water, air as well as soil. Though it can be utilized for different useful purposes, due to the lack of technical knowledge about how and proper motivation, no progress has been made in its utilization. It has been demonstrated that the fly ash can be used for making a value added catalyst zeolite beta by using simple and low cost process. In the present paper it is demonstrated that the fly ash can be used as a source of silica and alumina in the synthesis of value added catalyst zeolite beta. Moreover, the influence of different silica sources such as tetraethylortho silicate, silica sol and fumed silica on the physiochemical characteristics of well crystallized zeolite beta was also studied. The detailed characterization was carried out by using powder XRD, (27)Al and (29)Si MAS NMR, chemical analysis and low temperature nitrogen adsorption. Based on the data obtained from various systems containing different silica source, fumed silica is found to be most efficient source materials and showed superiority in the uniformity of aluminum distribution and possesses higher surface area.